2021
DOI: 10.1002/rhc3.12234
|View full text |Cite
|
Sign up to set email alerts
|

Trust and confidence in authorities, responsibility attribution, and natural hazards risk perception

Abstract: Risk perception varies across contexts like different risk agents and cultures. The roles of trust, confidence in authorities, and responsibility attribution in natural hazards risk perception are understudied. In this paper, the correlations between trust in authorities, confidence in authorities, responsibility attribution, and natural hazards (typhoon and earthquake) risk perception are explored using an updated representative data set from Taiwan (the 2013 and 2019 Taiwan Social Change Survey). The perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…People who face unfamiliar natural hazards rely more on expert sources to evaluate information, make risk judgments, and take preparedness actions. In this sense, if people face known natural hazards, trust may not influence risk judgments and preparedness measures (DeYoung & Peters, 2016;Han et al, 2021;Paton, 2007Paton, , 2008.…”
Section: Trust In Authoritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…People who face unfamiliar natural hazards rely more on expert sources to evaluate information, make risk judgments, and take preparedness actions. In this sense, if people face known natural hazards, trust may not influence risk judgments and preparedness measures (DeYoung & Peters, 2016;Han et al, 2021;Paton, 2007Paton, , 2008.…”
Section: Trust In Authoritiesmentioning
confidence: 99%
“…However, trust may not significantly influence risk judgments or motivation to take preparedness measures if people face known hazards. Based on their prior experience, they may consider the information they hold as sufficient to face a threat (DeYoung & Peters, 2016; Han et al., 2021; Paton, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In studies on risk perception and acceptance of danger, trust is considered an explanatory variable 36 . The relationship between trust and risk perception is studied by risk management researchers and it has been found that individuals' risk perceptions show differences based on cultural context and risk factors and there is a strong connection between perceived risk probability and trust 37,38 .…”
Section: Trustmentioning
confidence: 99%
“…Alacahan O. / Cumhuriyet Medical Journal, 45(1):[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]2023 …”
mentioning
confidence: 99%
“…An implicit degree of confidence is connected with each attribution made at the same moment. 92 , 93 Researchers must concentrate on how each attribution foresees feedback outcomes, despite employees demonstrating distinct personality features when they make mixed-up attributions. For example, an employee may believe that their boss offers them negative feedback to help them perform better, but they may also think that the supervisor is in an evil mood.…”
Section: Limitations and Future Researchmentioning
confidence: 99%